Analyzing the Key Responsible Factors: Cyber Security in Pakistan - Usmani, Muhammad Ahmad (Journal of Pakistan Administration, 2023)
This policy paper provides a comprehensive examination of Pakistan's current cybersecurity landscape, highlighting the main hurdles confronting the nation in this realm. It reviews the existing cybersecurity framework, including the Prevention of Electronic Crimes Act 2016 (PECA) and the National Cybercrime Policy 2021, while also identifying shortcomings and vulnerabilities within the system. The paper offers suggestions to address the escalating dangers and difficulties in the online environment, aiming to maintain a protected and durable online realm for individuals universally. To implement these suggestions, specific tactics are proposed. Embracing these actions and tactics can strengthen Pakistan's cybersecurity framework, protect critical infrastructure, and establish a secure and resilient cyberspace. This effort is crucial for securing the country, promoting economic stability, and improving the welfare of its inhabitants amidst continually changing cyber risks. In addition to the above, the paper discusses the importance of public-private partnerships in enhancing cybersecurity measures. It emphasies the need for collaboration between government agencies, private sector entities, and civil society organizations to effectively combat cyber threats. Furthermore, the paper explores the role of international cooperation in cybersecurity. It highlights the significance of bilateral and multilateral agreements in sharing information, conducting joint cyber exercises, and developing common cybersecurity standards. Moreover, the paper addresses the issue of capacity building in cybersecurity. It stresses the importance of training programs and awareness campaigns to equip individuals and organizations with the necessary skills and knowledge to mitigate cyber risks. Overall, this policy paper provides a holistic view of Pakistan's cybersecurity challenges and proposes practical solutions to enhance its cybersecurity posture. By implementing these recommendations, Pakistan can secure its cyberspace, protect its critical infrastructure, and ensure the safety and prosperity of its citizens in the digital age.
Keywords: Cyber Security; technology; Pakistan; Key Responsible Factors